The Effect Of Traffic Volume On Traffic Congestion Levels Along National Roads In Nias Regency, Indonesia - Muhammad Haris Zalukhu; Jun Fajar Krisman Giawa; Ignasia Hastuti Halawa (CV. SINAR HOWUHOWU, 2026)
Traffic congestion has become a major transportation challenge affecting mobility, economic activities, and regional accessibility, particularly along national roads that serve as primary transportation corridors. This study aims to analyze the effect of traffic volume on traffic congestion levels along national roads in Nias Regency, Indonesia. A quantitative descriptive approach combined with correlational analysis was employed to examine the relationship between traffic volume and roadway operational performance. Primary data were collected through manual traffic surveys conducted during morning, midday, and evening observation periods over seven consecutive days. Vehicle counts were converted into Passenger Car Units (PCU) based on the Indonesian Highway Capacity Guidelines (PKJI 2023). Traffic congestion levels were evaluated using road capacity, Volume-to-Capacity (V/C) ratio, average travel speed, and Level of Service (LOS). The influence of traffic volume on congestion was analyzed using simple linear regression. The results indicated an average traffic volume of 1,535.5 PCU/hour, an estimated road capacity of 1,850 PCU/hour, and a V/C ratio of 0.83, corresponding to Level of Service (LOS) D, which represents unstable traffic flow approaching roadway capacity. Regression analysis produced a correlation coefficient (R = 0.914) and a coefficient of determination (R² = 0.835), indicating that approximately 83.5% of the variation in traffic congestion levels could be explained by traffic volume. The statistical test confirmed that traffic volume has a significant positive effect on traffic congestion along national roads in Nias Regency (p < 0.001). The study concludes that increasing traffic demand substantially reduces roadway operational performance and recommends integrated congestion management strategies, including traffic control optimization, roadside activity regulation, parking management, and long-term infrastructure improvements to support sustainable regional transportation.